Resting of cryopreserved PBMC does not generally benefit the performance of antigen-specific T Cell ELISPOT assays - Batoulis, Helena; Recks, Mascha S.; Karacsony, Edith; Zhang, Wenji; Subbramanian, Ramu A.; Lehmann, Paul V.; Kuerten, Stefanie (Cells, 2012)
T cell monitoring is increasingly performed using cryopreserved PBMC. It has been suggested that resting of PBMC after thawing, that is, culturing them overnight in test medium, produces higher antigen-induced spot counts in ELISPOT assays. To evaluate the importance of overnight resting, we systematically tested cryopreserved PBMC from 25 healthy donors. CEF peptides (comprising CMV, EBV and flu antigens) were used to stimulate CD8 cells and mumps antigen to stimulate CD4 cells. The data show that resting significantly increased antigen-elicited T cell responses only for CEF high responder PBMC. The maximal gain observed was doubling of spot counts. For CEF low responders, and for mumps responders of either low- or high reactivity levels, resting had no statistically significant effect on the observed spot counts. Therefore, resting is not a generally applicable approach to improve ELISPOT assay performance, but can be recommended only for clinical subject cohorts and antigens for which it has a proven benefit. Because resting invariably leads to losing about half of the PBMC available for testing, and because doubling the PBMC numbers plated into the assay reliably doubles the antigen-induced spot counts, we suggest the latter approach as a simple and reliable alternative to resting for enhancing the performance of ELISPOT assays. Our data imply that resting is not required if PBMC were cryopreserved and thawed under conditions that minimize apoptosis of the cells. Therefore, this study should draw attention to the need to optimize freezing and thawing conditions for successful T cell work. © 2012 by the authors; licensee MDPI, Basel, Switzerland.
CRIS-Team Scopus Importer:2022-08-05
Keywords: CEF; Cryopreservation; High-throughput; Mumps; T cells